Pathophysiological evaluation of the LRRK2 G2385R risk variant for Parkinson’s disease - Toshiki Tezuka; Daisuke Taniguchi; Mariko Sano; Tomoyo Shimada; Yutaka Oji; Taiji Tsunemi; Aya Ikeda; Yuanzhe Li; Hiroyo Yoshino; Jun Ogata; Kahori Shiba-Fukushima; Manabu Funayama; et al. (npj Parkinson's Disease, 2022)
Abstract Missense variants in leucine-rich repeat kinase 2 (LRRK2) lead to familial and sporadic Parkinson’s disease (PD). The pathological features of PD patients with LRRK2 variants differ. Here, we report an autopsy case harboring the LRRK2 G2385R, a risk variant for PD occurring mainly in Asian populations. The patient exhibited levodopa-responsive parkinsonism at the early stage and visual hallucinations at the advanced stage. The pathological study revealed diffuse Lewy bodies with neurofibrillary tangles, amyloid plaques, and mild signs of neuroinflammation. Biochemically, detergent-insoluble phospho-α-synuclein was accumulated in the frontal, temporal, entorhinal cortexes, and putamen, consistent with the pathological observations. Elevated phosphorylation of Rab10, a substrate of LRRK2, was also prominent in various brain regions. In conclusion, G2385R appears to increase LRRK2 kinase activity in the human brain, inducing a deleterious brain environment that causes Lewy body pathology.